Dermoscopy Update: Review of its Extradiagnostic and Expanding Indications and Future Prospects - Sidharth Sonthalia; Paola Pasquali; Mahima Agrawal; Poonam Sharma; Abhijeet K. Jha; Enzo Errichetti; Aimilios Lallas; Virendra N. Sehgal (Mattioli1885, 2019)
The technique of dermoscopy has come a long way since its inception for characterization of suspicious nevi for early detection of dysplastic changes in predisposed individuals. Not only has its scope expanded to aid in quick diagnosis of a majority of nonmelanocytic disorders of the skin, hair, and nails, but it is being rightfully exploited for a plethora of nondiagnostic uses. Its use in the diagnosis of various pigmentary, papulosquamous, and infectious disorders and disorders of the scalp and hair, nails, and mucosa bears testimony to the ongoing expansion of its protean indications across skin types. Dermoscopy has transformed the conventional approach to dermatological diagnosis from clinicopathological correlation to clinico-dermoscopic-pathological correlation. It aids in convincing an otherwise reluctant patient to agree to biopsy and guides the selection of optimum site for the same. Dermoscopic clues suggestive of stability or activity of the lesion and/or disease in various dermatoses are being accrued. Early assessment of therapeutic response to treatment is helpful for physicians, patients, and researchers conducting clinical studies. Aesthetic uses of dermoscopy are opulent and being explored. Dermoscopy has also provided the much-needed balancing act of interaction between practitioners and the new generation of patients. Last but not the least, dermoscopy has resulted in patients' better understanding of their disorders and improved compliance with treatment protocols.